Community Capacity Building and Crime Reporting in Lagos, Nigeria (Global Journal of Science Frontier Research, 2014)
Various reasons cause community residents not to report crimes to the police. This study examined the capacity to report crimes among residents of communities in Lagos, Nigeria within the functionalist framework. A combination of qualitative and quantitative approaches was adopted. The study was conducted in the three senatorial districts of Lagos. Data collection involved a survey of 948 respondents selected though a multistage sampling procedure, 6 In-Depth Interviews, 12 Key Informant Interviews and 10 Case Studies were conducted to elicit qualitative data. While quantitative data analysis involved the use of descriptive statistical tools, chi square and regression, qualitative data were content analysed. Findings show that 50.6% of respondents had no capacity to report crime due to ignorance and 48.2% because of pressures from social networks. Moreover, while 1.6% of respondents were less constrained to report crime to the police because they suspected the police, 33.2% were scared by police demand for bribes. The study concluded that victims were unaware that their relative safety depends on their ability to put local intelligence behind the police in solving crime. It recommends that government should criminalize stereotypes against reporting and include reporting capacity building norms in schools'curricula right from primary to tertiary levels.
Keywords: community capacity building; crime reporting; local intelligence; stereotypes; victims